Online-mobile service cross-channel cognitive evaluations in a multichannel context - J. Nel; C. Boshoff (South African Journal of Business Management, 2015)
Since the advent of mobile commerce, many firms have added a mobile (m-) service to their existing offline and online services. The adoption of an m-service in a multichannel context is not only influenced by factors directly associated with the m-service, but also by cross-channel cognitive evaluations emanating from other existing channels. These cross-channel evaluations can lead to evaluative synergies and dissynergies that can influence consumer decision-making. To explore empirically the impact of cross-channel synergies and dissynergies between the online service and the m-service offered by the same firm, against the background of expectation-transfer theory and status-quo-bias theory, data were collected from 666 online-service users. Consistent with expectation-transfer theory and status-quo-bias theory, the results of the study demonstrated that cross-channel evaluative synergies and dissynergies do indeed impact salient m-service beliefs. The results suggest that managers can leverage the cross-channel synergies emanating from online trust and ease-of-use beliefs to enhance the adoption of the m-service. The results also suggest that, to enhance wider adoption, the marketing managers of m-services need to mitigate the status-quo-bias effects emanating from online-service facilitating conditions, and lower online-service risk perceptions.
Keywords: 650